Job Satisfaction as Mediating on Perceptions of Organizational Support and The Commitment of Teacher Organizations - Arifudin, Slamet; Mora, Linda; Hakim, Arif Rahman (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
This study intends to find out whether job satisfaction can be a mediation when it is analyzed with perceptions of organizational support and organizational commitment of teachers at Islamic School X Karawang. Quantitative method with causality design is used in this research and sample selection uses non-probability sampling with total sampling. Data from 70 respondents were obtained through data collection with 8 Perceived Organizational Support Survey (SPOS) items with a reliability value of 0.954, 5 Satisfaction with Work Scale (SWWS) items with a reliability value of 0.883, and 24 Organizational Commitment Questionnaire (OCQ) items with a reliability of 0929. With the Structural Equations Modeling (SEM) feature of JASP software version 0.16, data analysis methods can be performed. The consequence of the investigation showed that perceived organizational support appeared to directly influence organizational commitment with a value of p=0.013 (p<0.05). Likewise, job satisfaction can mediate perceptions of organizational support and organizational commitment to teacher with a value of p<0.001 (p<0.05) so that it can be said that there has been partial mediation. The influence of perceived organizational support and job satisfaction on organizational commitment together is equal to 84.2%, while 15.8% is influenced by other variables not examined in this study.Penelitian ini bermaksud untuk mengetahui apakah kepuasan kerja dapat menjadi mediasi ketika dianalisis dengan persepsi dukungan organisasi dan komitmen organisasi guru di Sekolah Islam X Karawang. Metode kuantitatif dengan desain kausalitas digunakan dalam penelitian ini serta pemilihan sampel menggunakan non-probability sampling dengan sampling total. Data dari 70 responden didapatkan melalui pengumpulan data dengan 8 item Survei Perceived Organizational Support (SPOS) dengan nilai reliabilitas sebesar 0.954, 5 item Satisfaction with Work Scale (SWWS) dengan nilai reliabilitas sebesar 0.883, dan 24 item Organizational Commitment Questionnaire (OCQ) dengan nilai reliabilitas sebesar 0.929. Dengan fitur Structural Equations Modeling (SEM) dari software JASP versi 0.16 metode analisis data dapat dilakukan. Konsekuensi dari penyelidikan menunjukkan bahwa persepsi dukungan organisasi tampak langsung mempengaruhi komitmen organisasi dengan nilai p=0,013 (p<0,05). Demikian juga, kepuasan kerja dapat memediasi persepsi dukungan organisasi dan komitmen organisasi pada guru dengan nilai p=<0,001 (p<0,05) sehingga dapat dikatakan telah terjadi mediasi parsial. Besar pengaruh persepsi dukungan organisasi dan kepuasan kerja terhadap komitmen organisasi secara bersama-sama yaitu sebesar 84.2%, sedangkan sebesar 15.8% dipengaruh oleh variabel lain yang tidak diteliti pada penelitian ini.